PENGARUH KOMPRES HANGAT TERHADAP PERUBAHAN SUHU TUBUH PADA PASIEN ANAK HIPERTERMIA DI RUANG RAWAT INAP RSUD Dr. MOEWARDI SURAKARTA. - Purwanti, Sri; Ambarwati, Winarsih Nur (Jurnal Berita Ilmu Keperawatan, 2008)
Hipertermia represent circumstance where individual somebody experience of or berisiko to experience of increase temperature of continuous body higher the than 37,8°C ( 100°F) peroral or 38,8°C ( 101°F) perektal. This circumstance will generate trouble fullfiling of elementary requirement human being. To overcome this matter need immediately the self-supporting action treatment in the form of happened expected warm compress change of body temperature. In this research hence method of pre eksprerimen with device of one group pre test and post test data obtained to be analysed hence test t test, result got terjdi of change which signifikan that is with average of temperature of body 0,97°C by SD 0,35°C, value P = 0,001 which burden that P < 0,05. There influence of warm compress terhdap of change of temperature of body child of hipertermia space take care of to lodge RSUD Dr. Moewardi Surakarta